2015
DOI: 10.1038/nmeth.3404
|View full text |Cite
|
Sign up to set email alerts
|

A microfluidic device for label-free, physical capture of circulating tumor cell clusters

Abstract: Cancer cells metastasize through the bloodstream either as single migratory circulating tumor cells (CTCs) or as multicellular groupings (CTC-clusters). Existing technologies for CTC enrichment are designed primarily to isolate single CTCs, and while CTC-clusters are detectable in some cases, their true prevalence and significance remain to be determined. Here, we developed a microchip technology (Cluster-Chip) specifically designed to capture CTC-clusters independent of tumor-specific markers from unprocessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
598
1
3

Year Published

2015
2015
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 648 publications
(607 citation statements)
references
References 37 publications
(57 reference statements)
5
598
1
3
Order By: Relevance
“…Constructed from parylene-C, can process WB, captures viable cells, clusters observed Kaifi et al, 2015) 3D FaCTChecker Constructed from parylene-C, captures viable cells between membrane layers Parsortix Viable cells released by reversing flow Resettable Cell Trap Pneumatically-controlled microvalves (Qin et al, 2015) Cluster Chip Triangular pillars designed for CTC clusters (Sarioglu et al, 2015) Biophysical e Inertial Focusing Cells are passively separated by size through the application of inertial forces in microfluidic devices that affect positioning within the flow channel.…”
Section: D Track-etched Isetmentioning
confidence: 99%
See 1 more Smart Citation
“…Constructed from parylene-C, can process WB, captures viable cells, clusters observed Kaifi et al, 2015) 3D FaCTChecker Constructed from parylene-C, captures viable cells between membrane layers Parsortix Viable cells released by reversing flow Resettable Cell Trap Pneumatically-controlled microvalves (Qin et al, 2015) Cluster Chip Triangular pillars designed for CTC clusters (Sarioglu et al, 2015) Biophysical e Inertial Focusing Cells are passively separated by size through the application of inertial forces in microfluidic devices that affect positioning within the flow channel.…”
Section: D Track-etched Isetmentioning
confidence: 99%
“…Sarioglu et al recently reported the development of a novel three-dimensional microfiltration system specifically designed to capture CTC clusters called the Cluster-Chip (Sarioglu et al, 2015). Multiple studies using microfiltration for CTC isolation have reported capturing CTC clusters (aka microemboli) (Desitter et al, 2011;Harouaka et al, 2014;Ilie et al, 2014;Vona et al, 2000).…”
Section: Three-dimensional Microfiltration Systemsmentioning
confidence: 99%
“…Also known as circulating tumor microemboli, clusters immunomagnetically captured usng the CELLSEARCH platform have been identified in more than 30% of patients with small cell lung cancer and appear to lack apoptotic or proliferating cells, perhaps offering a survival advantage (84). The use of a new device, the Cluster-Chip, offers label-free isolation of CTC clusters with the use of triangular pillars acting as microfluidic "cluster traps" (85). This method showed that clusters were identified in 30% to 40% of patients with metastatic melanoma, breast cancer, and prostate cancer, with the majority of clusters containing 2 to 10 cells, although sometimes up to 19 cells.…”
Section: Ctcs and Propensity For Metastatic Colonizationmentioning
confidence: 99%
“…Similarly, circulating cancer-associated macrophage-like cells from patients with metastatic breast, prostate, and pancreatic cancers can disseminate into the circulation and interact with CTCs (90), with some observed to migrate bound to CTCs, potentially facilitating distant colonization and neovascularization. CTC clusters may express markers associated with platelet transcripts and/or tissue-derived macrophages, but not T/B/natural killer (NK) cells (85). Refinements in our ability to interrogate CTCs and associated cells may enable more rapid clinical development of targeted agents that can affect the metastatic cascade.…”
Section: Ctcs and Propensity For Metastatic Colonizationmentioning
confidence: 99%
“…Taking advantage of tumor-specific physical and biological properties, such as sizes and surface biomarkers, multiple technologies have been developed to capture and isolate single CTCs and CTC clusters [5][6][7] . However, most of these existing technologies require blood to be drawn to isolate and capture CTCs ex vivo, reducing the effective CTC detection sensitivity.…”
Section: Introductionmentioning
confidence: 99%